2016
DOI: 10.1016/j.jarmac.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

How fuzzy-trace theory predicts true and false memories for words, sentences, and narratives.

Abstract: Fuzzy-trace theory posits independent verbatim and gist memory processes, a distinction that has implications for such applied topics as eyewitness testimony. This distinction between precise, literal verbatim memory and meaning-based, intuitive gist accounts for memory paradoxes including dissociations between true and false memory, false memories outlasting true memories, and developmental increases in false memory. We provide an overview of fuzzy-trace theory, and, using mathematical modeling, also present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
117
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(132 citation statements)
references
References 91 publications
(137 reference statements)
9
117
0
2
Order By: Relevance
“…Semantic representations are capable of capturing important structural features of the world at many different levels of abstraction, which allows for rapid and flexible responses to a diverse array of environmental challenges. This preexisting knowledge structure guides ongoing cognition, which usually aids performance, but under some circumstances can lead us into error (1)(2)(3). A striking example is the widely studied DRM (Deese, Roediger, and McDermott) false-memory illusion (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Semantic representations are capable of capturing important structural features of the world at many different levels of abstraction, which allows for rapid and flexible responses to a diverse array of environmental challenges. This preexisting knowledge structure guides ongoing cognition, which usually aids performance, but under some circumstances can lead us into error (1)(2)(3). A striking example is the widely studied DRM (Deese, Roediger, and McDermott) false-memory illusion (4,5).…”
mentioning
confidence: 99%
“…However, a mechanistic understanding of how these regions generate false memories is lacking. In particular, although it is known that the semantic relatedness between the different words drives the illusion (3,6,7), little is known about the neural basis of this semantic relatedness. Computational models of semantic cognition propose that concepts are represented by a similarity-based code in an amodal "semantic hub," situated in the apex of the ventral processing stream in the temporal pole (TP) (17,18).…”
mentioning
confidence: 99%
“…Fuzzy trace theory provides an account of false recollection in the DRM paradigm (termed “phantom recollection” in this theory) that is based on two types of representations being formed during encoding: verbatim and gist-based traces (Brainerd, Wright, Reyna, & Mojardin, 2001; Reyna & Brainerd, 1995; Reyna, Corbin, Weldon, & Brainerd, 2016). The general meaning of the studied event is known as a gist trace, while the representation of details of the studied item, including perceptual information such as that manipulated in source memory studies, is known as a verbatim trace.…”
mentioning
confidence: 99%
“…This could be viewed as a point in favour of the associative view. However, it has been found that it is possible induce false memories that have a vivid phenomenology, that are characterised as ''mentally re-experienced'', by repeatedly presenting different words with the same meaning (Reyna et al 2016). This suggests that gist representations can be implicated in the production of false memories that involve being able to mentally re-experience; through strengthening the gist representation it is possible to induce participants to falsely believe that they can ''mentally re-experience'' a word.…”
Section: Epistemic Benefits Of Cognitive Mechanisms Underpinning the mentioning
confidence: 99%